INTEGRITAS PENGHULU DALAM PELAYANAN NIKAH: Memotret Pelayanan Publik Pada Kantor Urusan Agama Kecamatan Sebagai Bentuk Reformasi Birokrasi - Zainal Abidin; Arif Effendi (MAMBA'UL 'ULUM, 2022)
Abstract: The bureaucratic reform program has opened new public colors in Indonesia. Various government agencies have been conducting reforms in various sectors that have been a weak point for public services. One of them is public service to the ministry of religious affairs. The religious ministry continues to work on wedding services at the district office of religious affairs (KUA). The district office of religious affairs, has been tidying up to the changes that become the necessity of bureaucratic reform. One of the fundamental changes is a new form of wedding service. Today the implementation of public services is still faced with conditions that have not been in accordance with the needs and changes in various areas of life in society. Various cases such as illegal charges and gratification indicate the lack of integrity that some of the Penghulu in district office of religious affairs. Therefore, it takes the role of various elements to continue to coaching in building the integrity of district office of religious affairs employees, especially on Penghulu.